Cellulose-Keratin Supramolecular Composite: Conformation by Combined Fourier Transform Spectroscopy and Partial Least Square Regression Coefficient - Mushi , Ngesa E. (Tanzania Journal of Engineering and Technology, 2025)
Keratin and cellulose are important nano components with excellent mechanical and biological properties. However, the preparation route through dissolution in organic solvents to make manmade materials is challenging because of their intensive bonding interaction characteristics. Structural modification of the natural attributes is difficult to maintain after polymer regeneration. A new technique by a green route was devised to dissolve keratin from wool, hair, and feather with cellulose in situ using 1-Butyl-3-methylimidazolium chloride [BMIm] + Cl- ionic liquid as a solvent. The mixture of keratin and cellulose homogeneously and synergistically resulted in a supramolecular composite film through non-derivatized mechanochemical interactions. The structural properties of α–helix and β sheets of the regenerated keratin investigated using a Fourier transform spectroscope under transmission mode showed a successful regeneration. Using chemometrics software, the partial least square regression coefficient technique (PLSR) predicted the realistic α–helix and β-sheet content values. Wool showed the highest α–helix, and feathers demonstrated minor content of the secondary structure after regeneration. Regarding the β-sheet form, the feather has regained the most and wool the little content after regeneration. Our data is impressively good compared to the reported results for wool (the highest value was 33 % of the helix for wool) in the literature. The highest values were 52 % for α–helix from wool and 44 % β-sheet for the feather. As expected for all the keratin sources, the α–helix structure decreased, and the β-sheet form increased with the cellulose content. The use of biopolymers and the high temperatures for dissolution is exciting. The preparation route of supramolecular films to achieve multifunctional properties such as strength and biological activities is an inspiration to the green route akin the polymer melt processing techniques.